Prevention programs for alcohol consumption and abuse. (Journal of Parents and Teachers, 2014)
The consumption and abuse of alcohol among young people has launched a social alarm. However, the data confirm that alcohol consumption in the last five years has stabilized, although there is still a long way to go. The harmful effects of alcohol on youth can be avoided by educating adolescents in an integral way. The article gives guidelines on how to perform this complex task.
Keywords: Alcohol; youth; social alarm; harmful effects; comprehensive education; guidelines and guidelines for families.